The Quality of Bali Beef from East Nusa Tenggara during Distribution Process from Slaughterhouse to Consumers - A. Martiana; I. I. Arief; H. Nuraini; E. Taufik (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The aims of this study were to analyze the physicochemical quality and microbiological condition of Bali beef during distribution process from slaughterhouse to consumers. The study used six heads of Bali cattle from East Nusa Tenggara which were transported by Camara Nusantara cattle ship from East Nusa Tenggara (Kupang) to Tanjung Priok then they were slaughtered at Jatimulya slaughterhouse. Samples were taken from three points distribution: 1) at slaughterhouse, 2) at market, 3) at consumers’ freezer (beef after 3 days at consumers’ freezer). Observation on pH, water holding capacity, cooking loss and tenderness was done to measure the physicochemical quality of Bali beef. In terms of microbiology quantitative analysis of total plate count Escherichia coli, Staphylococcus aureus, and Salmonella sp were done on Bali beef. All data were analyzed statistically using two-way analysis of variance (ANOVA). The results showed that Bali beef during distribution had normal pH value ranges between 5.43 - 5.57, water holding capacity ranges between 37.1%-38.9%, tenderness ranges between 6.02-8.35 and cooking loss range between 40.26% - 49.72%. Total plate count showed that the number of Escherichia coli, Staphylococcus aureus, and Salmonella sp. contaminated the Bali beef exceeds Indonesia national standard (3932:2008). However, the physicochemical quality of the beef was in the normal range. The characteristics of Bali beef at three points above mentioned are normal pH, stable water holding capacity, high level of tenderness, and low level of cooking loss.